2017
DOI: 10.1051/epjconf/201713801010
|View full text |Cite
|
Sign up to set email alerts
|

Graviton mass bounds from an analysis of bright star trajectories at the Galactic Center

Abstract: Abstract. In February 2016 the LIGO & VIRGO collaboration reported the discovery of gravitational waves in merging black holes, therefore, the team confirmed GR predictions about an existence of black holes and gravitational waves in the strong gravitational field limit. Moreover, in their papers the joint LIGO & VIRGO team presented an upper limit on graviton mass such as m g < 1.2 × 10 −22 eV . So, the authors concluded that their observational data do not show any violation of classical general relativity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 130 publications
1
8
0
Order By: Relevance
“…A precession of orbit in Yukawa potential is in the same direction as in GR, but dependences of precession angles on semi-major axis and eccentricity are different in these two models, therefore, after observations of bright star orbits for one or a few periods one could select the best fit from two considered cases. In paper [4] we presented an upper bound for graviton mass 2.9×10 −21 eV using previous observations of S2 star (see also [108][109][110][111][112] for a more detailed discussion) and now we also demonstrate our forecasts to reduce this upper limit. As it was noted earlier, our current estimates for graviton mass is slightly weaker than the LIGO ones, but it is independent and consistent with LIGO results and we expect that the graviton mass estimate will be significantly improved with new observations.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A precession of orbit in Yukawa potential is in the same direction as in GR, but dependences of precession angles on semi-major axis and eccentricity are different in these two models, therefore, after observations of bright star orbits for one or a few periods one could select the best fit from two considered cases. In paper [4] we presented an upper bound for graviton mass 2.9×10 −21 eV using previous observations of S2 star (see also [108][109][110][111][112] for a more detailed discussion) and now we also demonstrate our forecasts to reduce this upper limit. As it was noted earlier, our current estimates for graviton mass is slightly weaker than the LIGO ones, but it is independent and consistent with LIGO results and we expect that the graviton mass estimate will be significantly improved with new observations.…”
Section: Discussionmentioning
confidence: 52%
“…In paper [4] we presented an upper bound for graviton mass 2.9×10 −21 eV using previous observations of S2 star (see also [108][109][110][111][112] for a more detailed discussion) and now we also demonstrate our forecasts to reduce this upper limit. As it was noted earlier, our current estimates for graviton mass is slightly weaker than the LIGO ones, but it is independent and consistent with LIGO results and we expect that the graviton mass estimate will be significantly improved with new observations.…”
Section: Discussionmentioning
confidence: 52%
“…46 If we apply our consideration for gravity theories with massive graviton and we use observational data for S2 star we obtain that 2.9 × 10 −21 eV with 90% C.L. 47 (see also discussion [48][49][50] ). Our estimate for graviton mass is slightly weaker than the LIGO ones, but it is independent and consistent with LIGO results.…”
Section: Graviton Mass Constraints From Analysis Of Trajectories Of Bmentioning
confidence: 88%
“…46 If we apply our consideration for gravity theories with massive graviton and we use observational data for S2 star we obtain that 2.9 × 10 −21 eV with 90% C.L. 47 (see also discussion [48][49][50] ).…”
Section: Graviton Mass Constraints From Analysis Of Trajectories Of B...mentioning
confidence: 88%
“…Second, as it was noted that if a graviton has a non-vanishing mass then there exists an additional time delay between electromagnetic and gravitational wave signals, so there is another opportunity to evaluate a graviton mass. Based on analysis of S2 orbit data obtained with VLT and Keck telescopes we found that at the 90% confidence level we have λ g > 2900 AU= 4.3 × 10 11 km or m g < 2.9 × 10 −21 eV [124,125,126,127]. In February 2016 the LIGO-Virgo collaboration published a couple of works where the authors reported the discovery of gravitational waves from mergers of…”
Section: Constraints On Massive Graviton Theorymentioning
confidence: 99%